2022
DOI: 10.3390/v14071414
|View full text |Cite
|
Sign up to set email alerts
|

Weekly Nowcasting of New COVID-19 Cases Using Past Viral Load Measurements

Abstract: The rapid spread of the coronavirus disease COVID-19 has imposed clinical and financial burdens on hospitals and governments attempting to provide patients with medical care and implement disease-controlling policies. The transmissibility of the disease was shown to be correlated with the patient’s viral load, which can be measured during testing using the cycle threshold (Ct). Previous models have utilized Ct to forecast the trajectory of the spread, which can provide valuable information to better allocate r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…[ 2 ] 2021 USA To develop a new method that uses information inherent in Ct values from RT-qPCR tests to robustly estimate the epidemic trajectory from multiple or even a single cross-section of positive samples Real-time Single unit/closed system Single unit followed by regional The local epidemic trajectory of SARS-CoV-2 was accurately estimated from Ct values of routine hospital admissions Khalil et al. [ 26 ] 2022 Lebanon To use data-driven modeling that utilizes Ct values and previous number of cases to forecast the trajectory of the spread of COVID-19 Retrospective analysis Single unit / local National A polynomial regression and support vector machine regression model using Ct values demonstrated potential for predicting COVID-19 incidences in institutions Lin et al. [ 24 ] 2022 China To analyze the viral load data on confirmed cases during two local epidemics in Hong Kong to explore the possibility of a correlation between temporal changes in the distribution of viral loads (measured by RT-qPCR Ct values) and estimates of R t based on case counts Real-time Local Local A log linear regression was fitted to daily incidence-based R t , on daily mean and skewness of Ct values at sampling during the third wave (considered the training period for this study) for real-time assessment of COVID-19 transmission in the community using Ct values.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 2 ] 2021 USA To develop a new method that uses information inherent in Ct values from RT-qPCR tests to robustly estimate the epidemic trajectory from multiple or even a single cross-section of positive samples Real-time Single unit/closed system Single unit followed by regional The local epidemic trajectory of SARS-CoV-2 was accurately estimated from Ct values of routine hospital admissions Khalil et al. [ 26 ] 2022 Lebanon To use data-driven modeling that utilizes Ct values and previous number of cases to forecast the trajectory of the spread of COVID-19 Retrospective analysis Single unit / local National A polynomial regression and support vector machine regression model using Ct values demonstrated potential for predicting COVID-19 incidences in institutions Lin et al. [ 24 ] 2022 China To analyze the viral load data on confirmed cases during two local epidemics in Hong Kong to explore the possibility of a correlation between temporal changes in the distribution of viral loads (measured by RT-qPCR Ct values) and estimates of R t based on case counts Real-time Local Local A log linear regression was fitted to daily incidence-based R t , on daily mean and skewness of Ct values at sampling during the third wave (considered the training period for this study) for real-time assessment of COVID-19 transmission in the community using Ct values.…”
Section: Resultsmentioning
confidence: 99%
“…The GP model provided growth-rate estimates that followed those estimated using observed case counts for the whole state Khalil et al. [ 26 ] Hospital NR NR NR NR NR NR National daily COVID-19 confirmed case counts were obtained from the Lebanese Ministry of Public Health and Worldometers website NR 7-day There was a temporal delay between the observed Ct values and the incidence rate with a trough in mean Ct values (on October 8 2020) followed by an increase in case numbers 3 weeks later (on October 29 2020) There was an inverse correlation between mean Ct values and number of cases ( P < 0.001), (Spearman correlation) Six data-driven models that utilized Ct values and number of cases from a previous wave (training dataset) were used to predict the epidemic trajectory. This was evaluated using MSE The sequence-to-sequence model MSE = 0.025 The polynomial regression (OLS) and SVR MSE = 0.1596, and MSE = 0.16754, respectively Lin et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Ct values for cross-sectional samples collected from patient populations over a given time period are often indicative of the state of the epidemic, with lower average Ct values indicating a growing pandemic (12)(13)(14). Similar studies have also found that crosssectional trends in Ct values can act as indicators of the future trajectory of the pandemic (15,16). At the patient level, Ct values have been shown to provide a good estimate of how long a patient will remain contagious (10,17,18), and several studies have shown that lower Ct values (i.e., higher viral loads) can be correlated with symptomatic infection, morbidity, and mortality (9,14,19,20).…”
Section: Introductionmentioning
confidence: 91%